The Influence of Recruitment Training Motivation and Leadership Style on Improving Employee Performance - Atmabrata, Cahyadi; Mujahid, Mujahid; Muin, Sri Adrianti (Newinera Publisher, 2023)
This research aims to assess the impact of recruitment, training, motivation, and leadership style on employee performance. The employed research method is quantitative using a correlational approach. Through the analysis and collection of data derived from interviews, documents, and surveys. The research findings indicate a significant impact of the recruitment variable on employee performance, evidenced by a p-value of 0.000, which is less than 0.005. This indicates that variable X1 (Recruitment) exerts a positive and significant impact on variable Y (Employee Performance), as evidenced by the results of the second test using the Training variable. The findings from the third test indicate that the incentive variable x3 has a partial positive and significant effect on employee performance Y, with a p-value of 0.033, which is less than 0.005. The findings of testing the four variables concerning leadership style and employee performance indicate that 0.035 < 0.005, signifying a partial positive and significant influence of leadership style on employee performance. The simultaneous testing of variables—recruitment (x1), training (x2), motivation (x3), and leadership style (x4)—exerts a favorable and substantial impact on employee performance, as evidenced by a significance value of 0.000, which is less than 0.005. This research significantly contributes to employee performance, evidenced by a coefficient of determination of 0.915, or 91.5%. This indicates a general conclusion that recruitment, training, motivation, and leadership style influence employee performance at PT Surya Mas Ocean.